2007
DOI: 10.1037/0022-3514.93.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Who goes to the bargaining table? The influence of gender and framing on the initiation of negotiation.

Abstract: Unlike typical negotiation experiments, these studies investigated when men and women initiate negotiations in the absence of overt prescriptions to negotiate. Using a new experimental paradigm, the authors showed that the framing of situations is a critical driver of gender differences in initiating negotiations. Drawing on literature on language, power, and politeness, the authors argued that framing situations as opportunities for negotiation is particularly intimidating to women, as this language is incons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
280
6
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(304 citation statements)
references
References 58 publications
12
280
6
6
Order By: Relevance
“…Las mujeres muestran una menor propensión a iniciar negociaciones para alcanzar los puestos y oportunidades deseados y generalmente se encuentran con mayores costes sociales que los hombres cuando lo hacen (Babcock & Laschever, 2003;Bowles, Babcock & Lai, 2007;Small, Gelfand, Babcock & Gettman, 2007).…”
Section: Diferencias De Génerounclassified
See 1 more Smart Citation
“…Las mujeres muestran una menor propensión a iniciar negociaciones para alcanzar los puestos y oportunidades deseados y generalmente se encuentran con mayores costes sociales que los hombres cuando lo hacen (Babcock & Laschever, 2003;Bowles, Babcock & Lai, 2007;Small, Gelfand, Babcock & Gettman, 2007).…”
Section: Diferencias De Génerounclassified
“…In general, men demand and keep a greater number of leadership positions than women. Women are less likely to initiate negotiations to access the desired positions and opportunities and generally have greater social costs than men when they do (Babcock & Laschever, 2003;Bowles, Babcock & Lai, 2007;Small, Gelfand, Babcock & Gettman, 2007). …”
Section: Gender Differencesmentioning
confidence: 99%
“…In the psychology literature, it has been suggested that women earn less than their male counterparts because they avoid competitive negotiation and, as Babcock and Laschever (2003) point out, they simply "don't ask" for a pay increase. In a lab setting, the experiment of Small et al (2007) identifies a clear gender gap in the likelihood of initiating a negotiation, with women asking for a higher payment from the experimenter less often than men. Bowles et al (2007) study gender differences in negotiation in the presence of an evaluator, who can be male or female.…”
Section: Individual Preferencesmentioning
confidence: 99%
“…For this reason, we analyzed the data using repeated measures logistic regressions complemented with a generalized estimating equations (GEE) approach for each phase of the initiation process, specifying an exchangeable correlation structure (i.e., observations clustered within respondents without considering order) in all sets of dependent variables. As gender (Bear, 2011;Bowles et al, 2007;Small et al, 2007) and age (Volkema & Fleck, 2012) had been found in previous studies to relate to initiation behavior, they were controlled for in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to individual attributes, situational characteristics are perhaps the more malleable and influential of the two broad categories, capable of moderating the effects of personality/demographic factors (Small et al, 2007). As Bazerman, Curhan, Moore, and Valley (2000) argue in their review of research on negotiation, "slight changes in situational features swamp these [individual difference] effects" (p. 281).…”
Section: Introductionmentioning
confidence: 99%